Effect of the 11+ injury prevention programme on fundamental movement patterns in soccer players - Ezequiel Rey; Alexis Padrón-Cabo; Erik Penedo-Jamardo; Sixto González-Víllora (Termedia Publishing House, 2018)
No studies have assessed whether changes in an individual's fundamental movement patterns can be achieved with the 11+ prevention programme in soccer players. The aim of this study was to assess the effect of the 11+ compared with a standard warm-up on fundamental movement patterns using the Functional Movement Screen (FMS) in amateur male soccer players. Twenty-three male soccer players (age: 24.7±.3.8 years; height: 1.77±0.58 m; body mass: 73.9±6.2 kg) were randomly assigned to the 11+ (n= 12) or control (n= 11) group. The intervention programme had to be carried out 3 times a week over 6 weeks. The 11+ warm-up lasted ~25 minutes and was conducted before starting regular practice, replacing the team's standard warm-up. The control group warmed up with standard jogging, ball exercises, and active stretching to match the duration of the 11+. Within-group analysis revealed significant improvements in the FMS total score in the 11+ (+10.51%; d= 0.83) and control group (+7.99%; d= 0.68) from pre-test to post-test. In the between-group analysis, there were no significant differences between groups. At the post-test a significantly greater number of players in the 11+ group exhibited a score that improved to above the injury threshold (≤14) (p= 0.046). This study suggests that regular implementation of the 11+ injury prevention programme may not produce additional improvements in fundamental movement patterns other than those produced by a standard warm-up.